Optimization of Ice Availability for the Catch of Fishermen in Bajo Village as an Effort to Support Asta Cita and Agromaritime Development in South Halmahera - Hardin Hardin; Nasir Haya; Julkarnain Ahmad (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
The purpose of this study is to optimize the availability of ice to support the catch quality of fishermen in Bajo Village. This research objective is divided into two parts: first, to identify the constraints in ice production and distribution faced by fishermen in Bajo Village; and second, to develop strategies for optimizing ice availability for the fishermen. The study focuses on strengthening the post-harvest supply chain, particularly in the aspect of fish catch preservation through improved ice availability in Bajo Village. The research employs a descriptive qualitative approach using a case study method combined with participatory observation and interviews. This method is used to gather information regarding the condition of ice availability in Bajo Village, its role in maintaining the quality of fishermen’s catch, and to formulate optimization strategies in support of the Asta Cita vision and the Agromaritime Halmahera Selatan concept. The analysis in this study combines both quantitative and qualitative approaches, with several formulated models to describe the relationship between ice availability and catch sustainability. These include the Analysis of Ice Production and Distribution Constraints and the Analysis of Ice Availability Optimization Strategies. The analysis shows that the current ice availability ratio is only 0.42 kg of ice per kg of fish. Based on this ratio, the estimated daily ice requirement is 416.67 kg. This situation indicates that ice availability is severely inadequate, risking a decline in the quality of the catch.